2021
DOI: 10.1111/jpy.13133
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic pollution promotes dominance by harmful cyanobacteria: A case study examining norfloxacin exposure in competition experiments

Abstract: Cyanobacterial harmful algal blooms (cyanoHABs) in freshwater lakes across the globe are often combined with other stressors. Pharmaceutical pollution, especially antibiotics in water bodies, poses a potential hazard in aquatic ecosystems. However, how antibiotics influence the risk of cyanoHABs remains unclear. Here, we investigated the effects of norfloxacin (NOR), one of the most widely used antibiotics globally, to a bloom‐forming cyanobacterium (Microcystis aeruginosa) and a common green alga (Scenedesmus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 86 publications
(92 reference statements)
0
4
0
Order By: Relevance
“…), accelerating community succession toward a cyanobacterial bloom . In other words, antibiotics have the potential to enhance the destructive effects of harmful algal blooms by disrupting interspecific interactions between cyanobacteria and other algae . Additionally, inducible defenses constitute an important source of heterogeneity in natural phytoplankton communities; such defenses are altered by antibiotics.…”
Section: Effects Of Antibiotics On Planktonic Communitiesmentioning
confidence: 99%
“…), accelerating community succession toward a cyanobacterial bloom . In other words, antibiotics have the potential to enhance the destructive effects of harmful algal blooms by disrupting interspecific interactions between cyanobacteria and other algae . Additionally, inducible defenses constitute an important source of heterogeneity in natural phytoplankton communities; such defenses are altered by antibiotics.…”
Section: Effects Of Antibiotics On Planktonic Communitiesmentioning
confidence: 99%
“…Here, we highlight an emerging venue based on intra- and inter-species communication/competition/allopathic interactions that take place between toxic cyanobacteria, non-toxic cyanobacteria (mainly Microcystis sp. ), and other organisms, mainly (but not only) green algae, that may ultimately lead to the development of mitigation protocols (see [ 66 , 75 , 89 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 ] and references therein). An emerging example is the reduction of cyanoHAB populations that enables the persistence dominance of various non-toxic algae.…”
Section: In-lake Treatmentsmentioning
confidence: 99%
“…Similarly, when both organisms were treated with the antibiotic norfloxacin, the inhibition of S . quadricauda was much stronger when Microcystis was also present [ 135 ]. These and many other reports suggest that exposure of Microcystis to stress enhances the intensity of interspecies interactions.…”
Section: In-lake Treatmentsmentioning
confidence: 99%
“…Some stressors in eutrophic waters include heavy metals, antibiotics, and dyes (Devarajan et al, 2015; Guo et al, 2020; Li et al, 2020). Despite the expected inhibitive effects of heavy metals on cyanobacterial growth (Richardson et al, 2018), some antibiotics are found to be promoting in two recent studies (Li et al, 2021; Xu et al, 2021). Here, three types of stress resistance are summarized in CyanoPATH: heavy metal and antibiotics, and mycosporine-like amino acids (MAAs) to shield ultraviolet light (Fig.…”
Section: Biological Functions Associated With Cyanohabsmentioning
confidence: 99%